Impact of Subliminally Presented Words Valence’ on Risk-Taking Decisions in a Game of Chance - Pastwa, Maciej W.; Imbir, Kamil K. (Frontiers in Psychology, 2019)
A positive mood is thought to accompany performing a risk-taking tendency, for instance in games of chance or gambling. This study concerns the impact of emotional stimuli presented in a subliminal manner on the riskiness of decisions made in a game of chance. The heights of stakes called in the game were adopted as the measure of risk taken. Special simulation of a real game of chance, based on coin tossing, was used for this experiment. The stimuli displayed subliminally were words differing in valence (three levels: negative, neutral, and positive). We expected that positive valence would provoke the riskiness of the subsequent decision. The main effect of the valence observed was that the subjects in positive word conditions bet higher stakes than in neutral and negative conditions. Positive emotions influenced the riskiness of decisions made by the subjects, which confirmed the set hypothesis. The results of the study, in addition to their theoretical implications, may have practical meaning due to realistic simulation of popular games of chance